Algorithm for a fixed charge telephone network approach transmitters placing problem - Lazaravičius, Saulius; Listopadskis, Narimantas (Lietuvos matematikos rinkinys, 2021)
Algorithm for a fixed charge telephone network approach transmitters placing problem is presented in this paper.